The effect of injection barrier on the open-circuit voltage of organic photovoltaic cells - Inche Ibrahim, Mohd Lukman (Elsevier, 2020)
The effect of injection barrier on the open-circuit voltage of organic bulk heterojunction photovoltaic devices is studied theoretically. When the injection barrier is more than 0.1 eV, the relationship between the injection barrier and the open-circuit voltage is simple and predictable where an increase in the injection barrier by a given amount in electronvolt leads to a decrease in the open-circuit voltage by approximately the same amount in volt. However, when the injection barrier is less than 0.1 eV, the effect of injection barrier on the open-circuit voltage is significantly more complicated, where the effect is influenced by the level of balance between the electron and the hole mobilities and the values of the mobilities, and weakly influenced by the light absorption rate. The results suggest that in order to maximize the open-circuit voltage, the injection barrier simply should not be larger than 0.1 eV under any conditions, and the injection barrier may need to be smaller than 0.1 eV under certain conditions depending the level of balance and the values of the carrier mobilities.